Pt(II) complex @mesoporous silica: preparation, characterization and study of release - (:unkn) unknown (BIOINTERFACE RESEARCH APPLIED CHEMISTRY, 2016)
Cisplatin analogs, having cytotoxic activity higher than that exerted by cisplatin, have recently triggered considerable interest by the community. The cis-[PtCl2(DMSO)HL] center dot 2DMSO, where HL = 7-amino-2-(methylthio)[1,2,4] triazolo[1,5-a] pyrimidine-6-carboxylic acid, has shown a potent cytotoxic activity on HepG2 hepatocarcinoma cells, while under identical conditions, it did not affect normal immortalized human liver cells (Chang). In this work, the above complex has been incorporated into MCM41 mesoporous silica, pure and functionalized with amino group, which is considered one of the best host for a drug delivery system for carrying high dosages of a variety of drugs in their mesopores. Since the controlled release of an anticancer drug helps to maintain its therapeutic level for an extended time period while minimizing undesirable high peaks immediately following administration, the in vitro tests have been performed in order to obtain the corresponding drug release profile. The investigated system demonstrated to be an efficient system for pharmaceutic controlled release. A deepened characterization of the systems has been performed in order to known their structure and features and to speculate the mechanisms involved in the release.
Keywords: MCM41; amino groups; Cisplatin analogs; XRD; Si-29 {H-1} CP-MAS NMR; controlled release; DRUG-DELIVERY; ROOM-TEMPERATURE; MCM-41; NANOPARTICLES; CISPLATIN; FUNCTIONALIZATION; AMINE